Organopolysiloxane composition for release paper or release film

By adding organic peroxide to the organopolysiloxane composition and optimizing the molar ratio of Si-H group and alkenyl groups, the problems of high amount of platinum group metal-based catalysts and difficulty in curing reactions in the prior art are solved, and a high-efficiency and low-cost release paper or release film process is achieved.

CN115279862BActive Publication Date: 2025-03-18SHIN ETSU CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180021359.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-16
Filing Date
2021-03-15
Publication Date
2025-03-18
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

The prior art requires a higher amount of platinum group metal catalyst in the process of peeling paper or peeling film, and when the components that hinder catalytic activity are contained, the curing reaction is difficult to proceed, resulting in high cost and insufficient peeling force.

Method used

By adding an appropriate amount of organic peroxide to the organopolysiloxane composition, the amount of platinum group metal-based catalyst is reduced, while optimizing the molar ratio of Si-H group and alkenyl group, improving the reaction speed and curability.

Benefits of technology

The addition reaction is carried out at a smaller amount of platinum group metal catalyst, forming a cured coating with the same peeling force, reducing manufacturing costs, and effectively curing on a substrate containing catalyst poison.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003846530530000171
    Figure BDA0003846530530000171
  • Figure BDA0003846530530000181
    Figure BDA0003846530530000181
  • Figure BDA0003846530530000182
    Figure BDA0003846530530000182
Patent Text Reader

Abstract

An organopolysiloxane composition for release paper or release film, comprising (A) an organopolysiloxane having two or more silicon-bonded alkenyl groups in one molecule, (B) an organohydrogenpolysiloxane having an average of two or more silicon-bonded hydrogen atoms (Si-H groups) in one molecule, (C) an organic peroxide, and a specific amount of (D) a platinum group metal catalyst. The composition can undergo an addition reaction with a smaller amount of the platinum group metal catalyst than in the past, and can form a cured film having the same release force as in the past, and can form a cured film using an addition reaction even on a substrate containing a catalyst poison component that could not be cured in the past.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organopolysiloxane composition for release paper or release film, which accelerates curing with a smaller amount of platinum group metal than conventional ones and can be cured even when containing a component such as amine that inhibits the catalytic activity of a platinum group metal catalyst. Background Art

[0002] Conventionally, in order to prevent adhesion and fixation between sheet substrates such as paper and plastic and pressure-sensitive adhesive materials, a cured film of an organopolysiloxane composition is formed on the substrate surface to impart release properties. The following method is known as a method for forming a cured organopolysiloxane film on the substrate surface.

[0003] (1) A method of forming a releasable coating by addition-reacting an alkenyl group-containing organopolysiloxane with an organohydrogenpolysiloxane using a platinum group metal compound as a catalyst (Patent Document 1: Japanese Patent Application Laid-Open No. 47-32072).

[0004] (2) A method of forming a releasable coating by condensing an organopolysiloxane having a functional group such as a hydroxyl group or an alkoxy group using an organic metal salt as a catalyst (Patent Document 2: Japanese Patent Publication No. 35-13709).

[0005] (3) A method of forming a releasable coating by radically polymerizing an acryl group-containing organopolysiloxane and a photoreaction initiator using ultraviolet rays or electron beams (Patent Document 3: Japanese Patent Application Laid-Open No. 54-162787).

[0006] Among the above-mentioned methods (1), (2), and (3), the method for forming a releasable coating using an addition reaction using a platinum group metal catalyst is widely used, which has excellent curability and can meet various requirements for peeling properties from low-speed peeling to high-speed peeling.

[0007] In the past, platinum group metal catalysts were often used at a platinum concentration of 50 to 400 ppm relative to the organopolysiloxane composition used for release paper or release film. This is because, when the platinum concentration is less than 50 ppm, the curing reaction does not proceed sufficiently, the cured film becomes soft, and the amount of residual Si-H groups is large, so the release force is improved. In addition, due to the presence of unreacted raw material organopolysiloxane, which becomes a transfer component, the organopolysiloxane is transferred to the pressure-sensitive adhesive surface attached to the release paper, causing a decrease in adhesive strength.

[0008] It is known that platinum group metal catalysts inhibit curing due to the mixing of phosphorus compounds, nitrogen compounds, sulfur compounds, and tin compounds in addition reactions. The mixing amount of the above-mentioned curing-inhibiting compounds sometimes works at a level of several ppm, and even if they are contained in a substrate such as paper or film in a trace amount, the curing of release paper is greatly inhibited.

[0009] Furthermore, platinum group metals are rare precious metals on earth and therefore expensive, and platinum group metal catalysts account for a large proportion of the cost of producing release paper or release film. Therefore, reducing the amount of platinum group metal catalysts leads to price reduction.

[0010] In addition reaction curing type silicone rubber compositions for liquid silicone resin adhesives, as addition reaction curing type silicone rubber compositions having resistance to curing inhibitors such as nitrogen compounds, sulfur compounds, and phosphorus compounds, there has been proposed a composition containing an organic peroxide having a 10-hour half-life temperature of 40° C. or higher (Patent Document 4: Japanese Patent Gazette No. 4314454).

[0011] However, in the addition reaction curing type silicone rubber composition for the liquid silicone resin adhesive, since the curing time is slowed down by the addition of an organic peroxide having a 10-hour half-life temperature of 40°C or higher, a composition containing a metal or a metal compound selected from copper, copper compounds, manganese, manganese compounds, iron, iron compounds, silver, and silver compounds and an acetylacetone compound has been proposed as another additive (Patent Document 5: Japanese Patent No. 4569753). However, the curing time in the examples is 10 to 100 minutes at 100°C, and cannot be used for release paper applications that must be cured within 60 seconds (preferably within 30 seconds).

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 47-32072

[0015] Patent Document 2: Japanese Patent Publication No. 35-13709

[0016] Patent Document 3: Japanese Patent Application Laid-Open No. 54-162787

[0017] Patent Document 4: Japanese Patent No. 4314454

[0018] Patent Document 5: Japanese Patent No. 4569753 Summary of the invention

[0019] Problems to be solved by the invention

[0020] The present invention has been made in view of the above circumstances, and its object is to provide an organopolysiloxane composition for release paper or release film, which can carry out an addition reaction with a smaller amount of platinum group metal catalyst than before, and further, even when containing a component that inhibits the catalytic activity of the platinum group metal catalyst, can form a cured film having a release force equivalent to that of the past, and further, can be cured by an addition reaction even in a substrate containing a catalyst poison component that has previously prevented the substrate from being cured.

[0021] Means for solving problems

[0022] The present inventors have conducted intensive studies to achieve the above object and have found that the above problems can be solved by adding 0.01 to 5 parts by mass of (C) organic peroxide to 100 parts by mass of (A) component in an addition reaction-curable organopolysiloxane composition, thereby completing the present invention.

[0023] In the addition reaction curing type silicone rubber composition for liquid silicone resin adhesive described in the above-mentioned background art, if an organic peroxide is added to the composition, the curing time becomes slow. The present inventors have conducted research and found that in the organopolysiloxane composition for release paper or release film of the present invention, the curing property (0.9 to 1.1 g / m2 of the organopolysiloxane composition for release paper or release film is applied on paper) is 2 , after heating in a dryer at 120°C for 30 seconds, the coated surface was wiped with a finger to observe the curing state. The test method of the embodiments and comparative examples is described in detail) and the curing time is faster.

[0024] The reason why the results were different from those of the addition reaction curing type silicone rubber composition for liquid silicone resin adhesives is presumed to be that the addition reaction curing type silicone rubber composition for liquid silicone resin adhesives is greatly different in that a large amount of silica and calcium carbonate are blended in the composition. In addition, when the curing is performed at the same temperature (120° C.) as the curing of the organopolysiloxane composition for release paper or release film, the organopolysiloxane composition for release paper or release film is cured in 30 seconds, while the addition reaction curing type silicone rubber composition for liquid silicone resin adhesives requires more than 1 hour, which also suggests a difference in reaction speed.

[0025] In addition, the organopolysiloxane composition for release paper or release film of the present invention does not contain silica etc. which are contained in the addition reaction curing type silicone rubber composition for the above-mentioned liquid silicone resin adhesive. Furthermore, compared with the H / Vi of 0.41 in the example of the above-mentioned Patent Document 5, the preferred range of H / Vi in the organopolysiloxane composition for release paper or release film of the present invention is as high as 1.2 to 3.0, and Si-H groups are in excess, which is also a major difference.

[0026] Therefore, the present invention provides the following organopolysiloxane composition for release paper or release film (hereinafter, sometimes simply referred to as organopolysiloxane composition).

[0027] [1] An organopolysiloxane composition for release paper or release film, comprising at least the following components (A) to (D).

[0028] (A) 100 parts by mass of an organopolysiloxane having two or more silicon atom-bonded alkenyl groups in one molecule,

[0029] (B) an organohydrogenpolysiloxane having an average of 2 or more silicon-bonded hydrogen atoms (Si—H groups) per molecule: an amount such that the number of moles of Si—H groups is 1 to 5 times the number of moles of alkenyl groups in the component (A);

[0030] (C) organic peroxide: 0.01 to 5 parts by mass based on 100 parts by mass of component (A); and

[0031] (D) Platinum group metal catalyst: The amount thereof is 1 to 500 ppm in terms of mass of the platinum group metal in the total of the components (A), (B), (C), and (D).

[0032] [2] The organopolysiloxane composition for release paper or release film according to [1], further comprising 0.01 to 5 parts by mass of (E) an addition reaction control agent based on 100 parts by mass of the component (A).

[0033] [3] The organopolysiloxane composition for release paper or release film according to [1] or [2], wherein the component (C) is a polyfunctional organic peroxide having two or more peroxide bonds in the molecule.

[0034] [4] The organopolysiloxane composition for release paper or release film according to any one of [1] to [3], wherein the 10-hour half-life temperature of the component (C) is 70° C. or higher and 120° C. or lower.

[0035] [5] The organopolysiloxane composition for release paper or release film according to any one of [1] to [4], wherein the organic peroxide of the component (C) is a peroxyketal.

[0036] [6] The organopolysiloxane composition for release paper or release film according to any one of [1] to [5], wherein the organic peroxide as the component (C) has an exothermic onset temperature observed in DSC of 100° C. or higher.

[0037] [7] The organopolysiloxane composition for release paper or release film according to any one of [1] to [6], wherein the flash point of the composition is 250° C. or higher.

[0038] Effects of the Invention

[0039] According to the present invention, an organopolysiloxane composition for release paper or release film can be provided, which can carry out addition reaction with a small amount of platinum group metal catalyst, and even when containing a component that inhibits the catalytic activity of the platinum group metal catalyst, and has the same release force as when the amount of catalyst is large. Thus, an organosilicon cured film can be formed even under conditions that were difficult to cure in the past, and the manufacturing cost can be greatly reduced. In addition, a cured film can be formed by addition reaction on a substrate containing a catalyst poison. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in detail.

[0041] [(A) ingredient]

[0042] The component (A) is an organopolysiloxane having two or more silicon atom-bonded alkenyl groups in one molecule, and one type thereof may be used alone or two or more types thereof may be used in appropriate combination. Examples of such organopolysiloxanes include those having a structure represented by the following formula (1).

[0043] M a M Vi b D c D Vi d T e T Vi f Q g (1)

[0044] (Wherein, M is R3SiO 1 / 2 , M Vi For R2PSiO 1 / 2 , D is R2SiO 2 / 2 , D Vi RPSiO 2 / 2 , T is RSiO 3 / 2 , T Vi For PSiO 3 / 2 , Q is SiO 4 / 2, R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bonds, and P is -(CH2) n -CH=CH2 (n is an integer of 0 to 6). a, b, d, and f are each independently 0 or a positive number, b, d, and f are not 0 at the same time, 2≤b+d+f≤500, c is a positive number of 10 to 27000, e is a positive number of 0 or less than 200, and g is a positive number of 0 or less than 1000.)

[0045] In the above formula (1), R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bond, preferably having 1 to 10 carbon atoms, and more preferably having 1 to 8 carbon atoms. Specifically, alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, and dodecyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl, naphthyl, and tolyl; aralkyl groups such as benzyl and phenethyl; and groups obtained by replacing a part of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms, epoxy groups, amino groups, polyether groups, cyano groups, hydroxyl groups, etc. Among them, in the case of maintaining the curability and reducing the peeling force of the obtained cured product, it is preferred that 80 mol% or more of the total number of R is methyl.

[0046] P is -(CH2) n Specific examples of the alkenyl group represented by -CH=CH2 (n is an integer of 0 to 6) include vinyl, allyl, butenyl, propenyl, 5-hexenyl, octenyl and the like, among which vinyl is preferred.

[0047] a, b, d, and f are each independently 0 or a positive number, b, d, and f are not 0 at the same time, and preferably 2≤b+d+f≤500, 2≤b+d+f≤200.

[0048] a is preferably a positive number of 0 or 1 to 100, more preferably a positive number of 0 or 1 to 50, b is preferably a positive number of 0 or 1 to 100, more preferably a positive number of 0 or 1 to 50, d is preferably a positive number of 0 or 1 to 500, more preferably a positive number of 0 or 1 to 300, and f is preferably a positive number of 0 or 1 to 100, more preferably a positive number of 0 or 1 to 50.

[0049] In addition, c is a positive number of 10 to 27000, preferably a positive number of 10 to 20000, and more preferably a positive number of 50 to 15000. When c is less than 10, the amount of mist generated increases when the coating speed reaches 200 m / min or more, and the coated surface of the organopolysiloxane composition may be rough. On the other hand, when c exceeds 27000, the kinematic viscosity of the organopolysiloxane composition becomes too high, the coating property decreases, and the smoothness deteriorates, and the difference in the coating amount may become large depending on the position.

[0050] e is a positive number of 0 or 200 or less, preferably a positive number of 0 or 20 or less, and more preferably a positive number of 0 or 10 or less. g is a positive number of 0 or 1000 or less, preferably a positive number of 0 or 10 or less, and more preferably a positive number of 0 or 5 or less.

[0051] The vinyl value of component (A) is preferably 0.001 to 0.7 mol / 100 g, more preferably 0.005 to 0.5 mol / 100 g, and even more preferably 0.01 to 0.1 mol / 100 g. If the vinyl value is less than 0.001 mol / 100 g, there may be too few reaction points to cause poor curing, and if the vinyl value exceeds 0.7 mol / 100 g, the crosslinking density may be too high, the low-speed peeling force may be too high, and peeling may be difficult.

[0052] The weight average molecular weight of component (A) is preferably 800 or more and 300,000 or less, more preferably 3000 or more and 280,000 or less. If the weight average molecular weight of component (A) is less than 800, the coating amount on the substrate sometimes becomes insufficient. In addition, if it exceeds 300,000, the workability is reduced. It should be noted that in the present invention, the weight average molecular weight can be measured by the weight average molecular weight converted by gel permeation chromatography (GPC) analysis (solvent: toluene) (the same below).

[0053] The kinematic viscosity of the component (A) at 25° C. measured with an Ostwald viscometer is preferably 7 mm 2 / s or more and 30 mass% toluene solution viscosity (kinematic viscosity of a solution obtained by dissolving 30 mass% of the organopolysiloxane in toluene) 70000 mm 2 / s or less, more preferably 50mm 2 / s or more and 30 mass% toluene solution viscosity 60000mm 2 / s or less. Kinematic viscosity is less than 7mm 2 / s, the coating amount becomes insufficient. In addition, the viscosity of the solution in 30 mass % toluene exceeds 70000 mm 2 / s, the workability is reduced.

[0054] Specific examples of such component (A) include polysiloxanes containing alkenyl groups at both ends, polysiloxanes containing alkenyl groups in side chains, polysiloxanes containing alkenyl groups at one end and in side chains, polysiloxanes containing alkenyl groups at both ends and in side chains, and branched polysiloxanes containing alkenyl groups at the ends.

[0055] If expressed in structural formula, M Vi 2D c 、M2D c D Vi d 、M Vi 3D cT1, M Vi 4D c T2, M Vi 2D c D Vi d 、M Vi 2D c Q1, M a D c D Vi d T Vi f (M、M Vi ,D,D Vi , T, T Vi , Q, a, c, d, f are the same as above. The same below) etc. As a more specific structural example, M Vi 2D 100 、M2D 97 D Vi 3. M2D 26 D Vi 4. M2D 96 D Vi 4. M2D 95 D Vi 5. M Vi 3D 100 T1, M Vi 4D 100 T2, M Vi 2D 97 D Vi 1. M Vi 2D 95 D Vi 3. M3D 93 D Vi 3T Vi 1. M Vi 2D 20000 、M2D 10000 D Vi 20 wait.

[0056] [(B) ingredient]

[0057] The component (B) is an organohydrogenpolysiloxane having an average of 2 or more silicon-bonded hydrogen atoms (Si-H groups) in one molecule, and one type thereof may be used alone or two or more types thereof may be used in appropriate combination. The Si-H groups of the organohydrogenpolysiloxane are subjected to an addition reaction with the alkenyl groups of the component (A) to form an organopolysiloxane crosslinked product.

[0058] The number of silicon-bonded hydrogen atoms (Si—H groups) is preferably 3 to 100, more preferably 10 to 100, per molecule.

[0059] The Si-H group content is preferably 0.001 to 3.5 mol / 100 g, more preferably 0.01 to 2.5 mol / 100 g, and even more preferably 0.02 to 2.0 mol / 100 g. If the Si-H group content is too low, curability and adhesion may be poor, while if it is too high, the peeling force may be increased.

[0060] The organohydrogenpolysiloxane as the component (B) is preferably an organohydrogenpolysiloxane having a structure represented by the following formula (2).

[0061] M h M H i D j D H k T L T H m Q n (2)

[0062] (Wherein, M is R3SiO 1 / 2 , M H For R2HSiO 1 / 2 , D is R2SiO 2 / 2 , D H RHSiO 2 / 2 , T is RSiO 3 / 2 , T H For HSiO 3 / 2 , Q is SiO 4 / 2 , R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and having no aliphatic unsaturated bonds. h, i, j, and L are independently 0 or a positive number, k is a positive number of 0 or less than 100, m is a positive number of 0 or less than 10, n is a positive number of 0 or less than 10, i, k, and m are not 0 at the same time, and 2≤i+k+m≤100. )

[0063] In the above formula (2), R can be exemplified by the same groups as those for R in the above formula (1), and among them, an alkyl group having 1 to 8 carbon atoms is preferred.

[0064] In formula (2), h, i, j, and L are each independently 0 or a positive number, h is preferably 0 or a positive number of 1 to 10, i is preferably 0 or a positive number of 1 to 10, j is preferably 0 or a positive number of 1 to 100, and L is preferably 0 or a positive number of 1 to 10. In addition, k is a positive number of 0 or 100 or less, preferably a positive number of 2 to 100, and more preferably a positive number of 10 to 80. m is a positive number of 0 or 10 or less, preferably a positive number of 0 or 5 or less, and n is a positive number of 0 or 10 or less, preferably a positive number of 0 or 5 or less. In addition, i, k, and m are not 0 at the same time, and i+k+m is a positive number of 2 to 100, preferably a positive number of 3 to 100, and more preferably a positive number of 10 to 80.

[0065] The weight average molecular weight of the component (B) is preferably 194 to 10000, more preferably 874 to 5000. If the weight average molecular weight of the component (B) is too small, the adhesion may be greatly deteriorated; if it is too large, the reactivity may be poor, the curing property may be reduced, and a reduction in the residual adhesion rate and an increase in the peeling force due to insufficient curing may be observed.

[0066] The kinematic viscosity of the component (B) at 25° C. measured with an Ostwald viscometer is preferably 2 to 500 mm 2 / s, more preferably 2 to 300 mm 2 / s, more preferably 5 to 200 mm 2 / s. The kinematic viscosity at 25°C is less than 2mm 2 / s, the reactivity is good due to the small molecular weight, but the adhesion to the substrate may be deteriorated. 2 / s, the reactivity may be poor, the curability may be reduced, and a reduction in the residual adhesive ratio or an increase in the peeling force due to insufficient curing may be observed.

[0067] Specific examples of such organohydrogenpolysiloxanes as the component (B) include polysiloxanes containing hydrosilyl groups at both terminals, polysiloxanes containing hydrosilyl groups at side chains, polysiloxanes containing hydrosilyl groups at one terminal and in side chains, and polysiloxanes containing hydrosilyl groups at both terminals and in side chains.

[0068] If expressed in structural formula, M H 2D j 、M2D H k 、M2D j D H k 、M H 2D j D H k 、M H 3D j T1, M H 4D j T2, M h D j D H k T H m (M、M H ,D,D H , T, T H , h, j, k, m are the same as above. The same below). Furthermore, as a specific structural example, M H 2D 10 、M H 2D100 、M2D 27 D H 3. M2D 97 D H 3. M2D 26 D H 4. M2D 25 D H 5. M2D 24 D H 6. M2D 96 D H 4. M2D 95 D H 5. M H 3D 100 T1, M H 4D 100 T2, M H 2D 97 D H 1. M H 2D 95 D H 3. M3D 93 D H 3T H 1. M2D H 30 、M2D H 60 wait.

[0069] The amount of component (B) is 1 to 5 times the molar number of alkenyl groups and Si-H groups in component (A), preferably 1.2 to 3 times. If the amount of component (B) is too small, the curing property and adhesion may be insufficient; if it is too large, the amount of remaining Si-H groups increases, so the peeling force may increase, and the Si-H groups decrease over time, and the peeling force decreases over time.

[0070] [(C) ingredient]

[0071] The component (C) is an organic peroxide, and although the mechanism is not clear, the addition reaction is carried out with a small amount of the platinum group metal catalyst, thereby having the effect of improving the activity of the platinum group metal catalyst. In addition, when the organopolysiloxane composition of the present invention contains a component that inhibits the catalytic activity of the platinum group metal catalyst, a cured film utilizing the addition reaction can be formed on a substrate containing a catalyst poison, and a cured film having a peeling force equivalent to that of a conventional one can be formed.

[0072] Examples of the organic peroxide include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxydicarbonates, peroxyesters, etc. Among them, polyfunctional organic peroxides having two or more peroxide bonds in the molecule, such as ketone peroxides and peroxyketals, are preferred, and peroxyketals are particularly preferred.

[0073] Among them, examples of peroxyketals include 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, 2,2-di(tert-butylperoxy)butane, n-butyl-4,4-di(tert-butylperoxy)valerate, 1,1-di(tert-amylperoxy)cyclohexane, 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-hexylperoxy)-2-methylcyclohexane, and 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane.

[0074] Then, although the reason is not clear, the curing property of the organic peroxide as the component (C) is particularly excellent when the 10-hour half-life temperature is 70° C. or higher and 120° C. or lower, and particularly when the 10-hour half-life temperature is 80° C. or higher and 110° C. or lower. The 10-hour half-life temperature mentioned here is a temperature obtained by preparing a 0.1 mol / L or 0.05 mol / L organic peroxide solution in benzene, sealing the solution in a nitrogen-substituted glass tube, immersing the solution in a thermostatic bath set at a predetermined temperature, and thermally decomposing the solution.

[0075] Examples of the organic peroxide having a 10-hour half-life temperature of 70° C. or higher and 120° C. or lower include the following.

[0076] 1,1-Di(tert-butylperoxy)cyclohexane: 90.7°C (measured concentration 0.1 mol / L)

[0077] 2,2-Di(tert-butylperoxy)butane: 103.1°C (measured concentration 0.1 mol / L)

[0078] 1,1-Di(tert-hexylperoxy)cyclohexane: 87.1°C (measured concentration 0.05 mol / L)

[0079] The exothermic start temperature of the component (C) measured by a differential scanning calorimeter (DSC) is preferably 100° C. or higher, more preferably 110 to 160° C. When the exothermic start temperature is lower than 100° C., the addition reaction may occur during summer storage and solidification may occur. The DSC measurement is performed at a temperature increase of 10° C. / min from 25° C. to 300° C.

[0080] Relative to 100 parts by mass of component (A), the amount of component (C) is 0.01 to 5 parts by mass, preferably 0.05 to 3 parts by mass, and more preferably 0.1 to 2 parts by mass. If it is less than 0.01 parts by mass, the curing acceleration effect is not obvious. On the other hand, if it exceeds 5 parts by mass, the transfer component increases, so the reduction of the residual bonding rate and the deterioration of the adhesion are observed. If the amount is too much, the curability deteriorates, so it is believed that the improvement of the curability caused by the organic peroxide is not caused by the polymerization reaction caused by dehydrogenation.

[0081] [(D) ingredient]

[0082] As (D) platinum group metal catalyst, a known catalyst used as an addition reaction catalyst can be used. Examples of such platinum group metal catalysts include platinum, palladium, rhodium, and ruthenium catalysts, and platinum catalysts are particularly preferred. Examples of the platinum catalyst include platinum silica·alumina, platinum alumina·halogen, platinum rhodium and other platinum compounds, complexes of platinum and vinyl siloxane, etc., alcohol solutions or aldehyde solutions of chloroplatinic acid, complexes of chloroplatinic acid and various olefins, complexes of chloroplatinic acid and vinyl siloxane, etc.

[0083] The organopolysiloxane composition of the present invention can be subjected to addition reaction with a smaller amount of platinum group metal catalyst than before. The amount of the component (D) is 1 to 500 ppm, preferably 1 to 200 ppm, and more preferably 1 to 150 ppm, based on the mass of the platinum group metal in the organopolysiloxane composition (i.e., the total of the components (A), (B), (C), and (D)). When the amount of the component (D) is less than 1 ppm, the addition reaction does not proceed, and a large amount of unreacted functional groups remain, so that a sufficient cured film is not formed. In addition, if it is more than 500 ppm, it may react with moisture or a control agent, or the usable time may be shortened, and curing may occur during operation.

[0084] [(E) ingredient]

[0085] (E) The addition reaction control agent is a component added as needed to control the catalytic activity of the platinum group metal catalyst, and examples thereof include various organic nitrogen compounds, organic phosphorus compounds, acetylene compounds, oxime compounds, organic chlorine compounds, etc. Specifically, examples thereof include acetylene alcohols such as 1-ethynyl-1-cyclohexanol, 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, and 2-phenyl-3-butyn-2-ol, acetylene compounds such as 3-methyl-3-pentene-1-yne, and 3,5-dimethyl-3-hexene-1-yne, reaction products of acetylene compounds such as 1,1-dimethylpropynyloxytrimethylsilane with alkoxysilane, siloxane, or hydrosilane, vinyl siloxanes such as tetramethylvinylsiloxane ring, organic nitrogen compounds such as benzotriazole, and other organic phosphorus compounds, oxime compounds, maleic acid compounds such as diallyl maleate, and organic chlorine compounds.

[0086] The amount of component (E) when mixed is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of component (A). If the amount is too little, the usable time may be shortened and curing may occur during operation; if the amount is too much, the addition reaction may not occur and a cured film may not be formed.

[0087] [Optional Ingredients]

[0088] The organopolysiloxane composition of the present invention may be formulated with an organic solvent. As the organic solvent, preferably used are organic solvents soluble in the organopolysiloxane such as toluene, hexane, xylene, methyl ethyl ketone (excluding siloxane solvents), low-viscosity cyclic siloxanes such as octamethyltetrasiloxane and decamethylpentasiloxane, M2D p (M and D are the same as above. p is 0 or a positive number of 200 or less, preferably a positive number of 1 to 50) and other linear siloxanes, M 2+q D p T q (M, D, and T are the same as above. p is a positive number of 0 or 200 or less, preferably a positive number of 1 to 50, and q is a positive number of 1 to 10, preferably a positive number of 1 to 3) and other branched siloxanes and other organopolysiloxanes (siloxane solvents).

[0089] The amount of the organic solvent used is preferably 3 to 50 times, more preferably 8 to 30 times the total mass of the components (A) and (B).

[0090] As optional additive components, for example, for the purpose of imparting slip properties, there can be mentioned high molecular weight linear type organopolysiloxane, and for the purpose of adjusting the release force, there can be mentioned silicone resins having an aromatic group, silicone resins, silica, and the like.

[0091] [Manufacturing method]

[0092] The organopolysiloxane composition of the present invention is obtained by mixing the above-mentioned components (A) to (D) and, if necessary, the component (E) and the respective predetermined amounts of the optional components. The organopolysiloxane composition of the present invention may contain components that are usually added to an organopolysiloxane composition for release paper or release film within a range that does not impair the effects of the present invention. It should be noted that the properties thereof will not be reduced even when diluted with an organic solvent.

[0093] The kinematic viscosity of the obtained organopolysiloxane composition at 25° C. measured by an Ostwald viscometer is preferably 50 to 1000 mm 2 / s, more preferably 100 to 500 mm 2 / s.

[0094] Furthermore, the organopolysiloxane composition for release paper or release film of the present invention is preferably a composition designated as a combustible or non-hazardous substance in the Fire Protection Act, and therefore the flash point of the organopolysiloxane composition is preferably 250° C. or higher. In order to make the flash point of the organopolysiloxane composition 250° C. or higher, for example, it is preferred to reduce the amount of a compound having a low flash point and to add a component having a high flash point.

[0095] [Purpose and usage]

[0096] After the organopolysiloxane composition of the present invention is applied to a sheet substrate such as paper or a plastic film by a coating roller (a three-roller, a five-roller, a gravure roller, a flat gravure roller, etc.), it is cured by heating by a conventional method. In this way, a silicone cured film of the organopolysiloxane composition of the present invention is formed on one side of the sheet substrate, which is suitable for use as a release sheet, etc. Examples of paper substrates include glassine paper, polyethylene laminated paper, polyvinyl alcohol resin coated paper, clay coated paper, etc. Examples of plastic films include films of polyethylene, polypropylene, polyethylene terephthalate, etc.

[0097] The amount of the organopolysiloxane composition applied may be an amount sufficient to form a cured silicone film on the surface of the sheet-like substrate, and is, for example, 0.1 to 5.0 g / m 2 Excessive coating may sometimes lead to a decrease in release performance.

[0098] The temperature during heat curing varies depending on the type of substrate and the coating amount, but a cured film can be formed on the substrate by heating at 80 to 200° C., preferably 100 to 180° C., for 60 to 1 second, preferably 30 to 2 seconds.

[0099] Example

[0100] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. 1 The kinetic viscosity is determined by H-NMR, the kinematic viscosity is a value measured using an Ostwald viscometer at 25°C, and the flash point is a value determined by the Cleveland open cup method (ISO 2592:2000, JIS K 2265-4:2007).

[0101] [Raw materials used]

[0102] (A)Ingredients

[0103] Methylvinyl polysiloxane (1)

[0104] The following structure has a vinyl value of 0.0166 mol / 100 g and a kinematic viscosity of 440 mm 2 / s polysiloxane

[0105] {(CH2=CH)(CH3)2SiO 1 / 2}2{(CH3)2SiO} 160

[0106] (B) Ingredients

[0107] Methyl hydrogen polysiloxane (2)

[0108] The Si-H content of the following structure is 1.62 mol / 100 g and the kinematic viscosity is 35 mm 2 / s methyl hydrogen polysiloxane

[0109] {(CH3)3SiO 1 / 2}2{(CH3)HSiO} 100

[0110] (C) Ingredients

[0111] PERHEXA HC (manufactured by NOF Corporation, 1,1-di(tert-hexylperoxy)cyclohexane, 10-hour half-life temperature 87.1°C, exothermic onset temperature 134°C, measured concentration 0.05 mol / L)

[0112] PERHEXA C (manufactured by NOF Corporation, 1,1-di(tert-butylperoxy)cyclohexane, 10-hour half-life temperature 90.7°C, exothermic onset temperature 134°C, measured concentration 0.1 mol / L)

[0113] (Other ingredients)

[0114] Leuco pigment: acts as a catalyst poison for platinum catalysts.

[0115] [Example 1]

[0116] 100 parts by mass of methylvinylpolysiloxane (1) as component (A), 1.77 parts by mass of methylhydrogenpolysiloxane (2) as component (B), 1 part by mass of PERHEXA C as component (C), and 0.3 parts by mass of 1-ethynyl-1-cyclohexanol as component (E) were added and stirred until uniform. Then, a complex of platinum and vinylsiloxane as component (D) was added in an amount of 100 ppm based on the mass of platinum atoms in the total mass of components (A), (B), (C), (D), and (E), and stirred until uniform. A mixture having a kinematic viscosity of 422 mm was prepared. 2 / s, H / Vi (ratio of Si-H groups in the composition to alkenyl groups in the composition) = 1.72, and a flash point of 277°C.

[0117] [Example 2]

[0118] A 2-hydroxy-1-nitro-1-ol-2-yl-2-nitro-1-ol-2 ... 2 / s, H / Vi=1.72, and a composition with a flash point of 275°C.

[0119] [Comparative Example 1]

[0120] A 2-hydroxy-1-nitropropene ester having a kinematic viscosity of 435 mm was prepared by using the same formulation as in Example 1 except that the component (C) was not added. 2 / s, H / Vi=1.72, and a composition with a flash point of 280°C.

[0121] [Comparative Example 2]

[0122] A 2-hydroxy-1-nitropropene ester having a kinematic viscosity of 434 mm was prepared by using the same formulation as in Example 2 except that the component (C) was not added. 2 / s, H / Vi=1.72, and a composition with a flash point of 278°C.

[0123] [Example 3]

[0124] The mixture was stirred in the same manner as in Example 1 except that the component (C) was changed to PERHEXA HC and the amount of the component (E) 1-ethynyl-1-cyclohexanol was increased to 0.5 parts by mass to prepare a product having a kinematic viscosity of 421 mm 2 / s, H / Vi=1.72, and a composition with a flash point of 264°C.

[0125] [Example 4]

[0126] The mixture was stirred in the same manner as in Example 1 except that the component (C) was changed to PERHEXA HC and the amount of the component (E) 1-ethynyl-1-cyclohexanol was increased to 0.8 parts by mass to prepare a product with a kinematic viscosity of 419 mm 2 / s, H / Vi=1.72, and a composition with a flash point of 252°C.

[0127] [Comparative Example 3]

[0128] The mixture was stirred in the same manner as in Comparative Example 1 except that the amount of 1-ethynyl-1-cyclohexanol as the component (E) was increased to 0.5 parts by mass, and a mixture having a kinematic viscosity of 422 mm was prepared. 2 / s, H / Vi=1.72, and a flash point of 267°C.

[0129] [Comparative Example 4]

[0130] The mixture was stirred in the same manner as in Comparative Example 1 except that the amount of 1-ethynyl-1-cyclohexanol as the component (E) was increased to 0.8 parts by mass, to prepare a mixture having a kinematic viscosity of 420 mm 2 / s, H / Vi=1.72, and a composition with a flash point of 258°C.

[0131] [Example 5]

[0132] In the blending composition of Example 1, 0.1 parts by mass of a leuco pigment was blended as an additive to prepare a granular material having a kinematic viscosity of 425 mm 2 / s, H / Vi=1.72, and a composition with a flash point of 277°C.

[0133] [Comparative Example 5]

[0134] In the compounding composition of Comparative Example 1, 0.1 parts by mass of a leuco pigment was added as an additive component to prepare a granular product with a kinematic viscosity of 427 mm 2 / s, H / Vi=1.72, and a composition with a flash point of 280°C.

[0135] The compositions obtained above were subjected to the following evaluations. The results are shown in Tables 1 to 3.

[0136] [Peel force]

[0137] The obtained composition was applied to the metal roller of the RI detector (manufactured by IHI Machinery Systems Co., Ltd.), and the two rollers consisting of the metal roller and the rubber roller were rotated for 45 seconds to uniformly stretch the composition, and then the composition was transferred from the rubber roller to the glass paper ASP (manufactured by Ahlstrom-Munksjo Co., Ltd.). The glass paper to which the composition was transferred was heated in a hot air dryer at 120°C for 30 seconds to obtain a glass paper having a thickness of 0.9 to 1.1 g / m 2After aging at 25°C for 24 hours, TESA-7475 tape (tesa UK Ltd.) was attached to the cured film surface of the release paper (from the transfer surface of the rubber roller) and cut into a size of 2.5 cm × 18 cm. The paper was sandwiched between a glass plate and heated at 25°C at 70 g / cm 2 Under load of 20g / cm2 and 70℃ 2 After aging for 24 hours under a load of, one end of the test piece was peeled off, and the end of the substrate with the pressure-sensitive adhesive of the TESA-7475 tape was stretched at an angle of 180 degrees relative to the glass paper at a peeling rate of 0.3 m / min. At this time, the force required for peeling (i.e., "peeling force") (N / 50mm) was measured using a tensile testing machine (AGS-50G manufactured by Shimadzu Corporation).

[0138] [Residual Adhesion Rate]

[0139] The TESA-7475 tape after the above peeling force measurement was attached to the polyester film, and a 2 kg roller was moved back and forth once to apply a load. After leaving it for 30 minutes, one end of the TESA-7475 tape was peeled off, and the end was stretched in a direction of an angle of 180 degrees relative to the polyester film, and peeled off at a peeling speed of 0.3 m / min. The force required for peeling at this time was measured: peeling force A (N / 25 mm).

[0140] As a blank test, an unused TESA-7475 tape was pasted on a polyester film, and a 2 kg roller was reciprocated once to apply a load as described above. After 30 minutes, one end of the TESA-7475 tape was peeled off, and the end was stretched in a direction of 180 degrees relative to the polyester film, and peeled off at a peeling speed of 0.3 m / min. The force required for peeling at this time was measured: peeling force B (N / 25 mm). The residual bonding rate (%) was calculated by (A / B)×100.

[0141] [Curing properties]

[0142] The obtained composition was applied to the metal roller of the detector, and two rollers consisting of a metal roller and a rubber roller were rotated in contact for 45 seconds to uniformly stretch the composition, and then the composition was transferred from the rubber roller to the polyethylene laminated paper. The polyethylene laminated paper to which the composition was transferred was heated in a hot air dryer at 120°C for 30 seconds to obtain a film having a thickness of 0.9 to 1.1 g / m 2 Remove the release paper from the dryer and immediately rub the cured film surface 10 times with your index finger, apply red marking ink, and observe the ink concentration and cured film state.

[0143] Regarding the results, the case where the fingerprints looked deep was marked as "×", the case where they looked light was marked as "△", and the case where they were hardly visible was marked as "○".

[0144] [Silicone transferability]

[0145] Similar to the case of the peeling force measurement, a polyethylene terephthalate film with a thickness of 36 μm was superimposed on the surface of the cured film of the composition obtained above formed on the surface of the polyethylene laminated paper, and after being pressed at 0.98 MPa for 20 hours at room temperature (25° C.), the polyethylene terephthalate film was removed from the cured film. An oily ink (trade name: MAGIC INK, manufactured by Teranishi Chemical Industry Co., Ltd.) was applied to the surface in contact with the cured film of the polyethylene terephthalate film, and the silicone transferability was evaluated according to the following criteria based on the shrinkage (ハジキ, cissing) thereof.

[0146] The results are indicated by "○" when there is no shrinkage due to ink (no silicone transfer or very little silicone transfer), and "×" when there is shrinkage due to ink (large silicone transfer).

[0147] [Table 1]

[0148]

[0149] [Table 2]

[0150]

[0151] [Table 3]

[0152]

[0153] In the above Table 3, the leuco pigment is a catalyst poison. The curability of Comparative Example 5, which removes PERHEXA C from the composition of Example 1 and adds 0.1 parts by mass of the leuco pigment, is poor, the uncured material is transferred, and the silicone transfer is large, the residual adhesion rate is also less than 80%, and the peeling force is also improved by nearly 3 times. In Example 5, which adds 1 part by mass of PERHEXA C to the composition of Comparative Example 5, despite the presence of the leuco pigment as a catalyst poison, the curability is improved, and the peeling force, residual adhesion rate, and silicone transfer are also good values.

Claims

1. An organopolysiloxane composition for release paper or release film, which contains at least the following components (A) to (D) without silicon dioxide or calcium carbonate, and has a kinematic viscosity of 100 to 500 mm at 25°C 2 / s, (A) 100 parts by mass of an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule, (B) an organohydrogenpolysiloxane having an average of 2 or more hydrogen atoms bonded to silicon atoms, i.e., Si-H groups, in one molecule: an amount such that the number of moles of Si-H groups is 1 to 5 times the number of moles of alkenyl groups in the component (A); (C) organic peroxide: 0.01 to 5 parts by mass based on 100 parts by mass of component (A); and (D) Platinum group metal catalyst: The amount thereof is 1 to 500 ppm in terms of the mass of the platinum group metal in the total of the components (A), (B), (C), and (D).

2. The organopolysiloxane composition for release paper or release film according to claim 1, wherein (E) 0.01 to 5 parts by mass of an addition reaction control agent is further contained based on 100 parts by mass of the (A) component.

3. The organopolysiloxane composition for release paper or release film according to claim 1 or 2, wherein The component (C) is a polyfunctional organic peroxide having two or more peroxide bonds in the molecule.

4. The organopolysiloxane composition for release paper or release film according to claim 1 or 2, wherein The 10-hour half-life temperature of the component (C) is 70° C. or higher and 120° C. or lower.

5. The organopolysiloxane composition for release paper or release film according to claim 1 or 2, wherein: The organic peroxide of the component (C) is a peroxyketal.

6. The organopolysiloxane composition for release paper or release film according to claim 1 or 2, wherein The organic peroxide of the component (C) has an exothermic onset temperature of 100° C. or higher observed in DSC.

7. The organopolysiloxane composition for release paper or release film according to claim 1 or 2, wherein: The flash point of the composition is 250°C or higher.

Citation Information

Patent Citations

  • Radiationncurable silicone release composition

    JP1979162787A

  • Autohesive thermosetting liquid silicone rubber composition

    JP2004107577A

  • Self adhesive thermosetting-accelerating-type liquid silicone rubber composition

    JP2006131813A

  • Heat curing type liquid silicone rubber composition

    JP2007106905A